Outspoken Cynics? Rethinking the Social Consciousness of Rap and Hip-Hop Music in Zimbabwe. Issue 1 (2nd January 2017) - Ncube, Gibson; Chipfupa, David
ABSTRACT: Rap and hip-hop are often characterised as musical genres replete with foul language, hyper-masculinity, misogyny, violence and egocentrism. The music of two Zimbabwean rappers Outspoken Tha Humble Neophyte (Tongai Leslie Makawa) and Synik (Gerald Mugwenhi) differs considerably from this stereotypical perception of rap and hip-hop. This article argues that the music of these two rappers is transcendental in its depiction and critique of life in contemporary urban Zimbabwe. Concentrating on two albums by these artists, the article examines how the music goes beyond entertainment as it offers a socio-political and cultural critique and self-reflexive space of thinking through diverse issues afflicting modern-day Zimbabwe. In a country where the public sphere is heavily censored by the state, making open and sincere discussions impossible, the music of these two artists proposes an alternative space to think through various matters. The article contends that music has the "illocutionary force" to unsettle ways of thinking, knowing and understanding the diverse and complicated realities we so often experience.